Pengaruh Strategi Pemasaran Terhadap Penjualan Batubara Pada PT. Cahaya Mantingan Nusantara Jakarta - Iskandar, Khalid; Andriyani, Wilan (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82)DO - 10.24843/JEKT.2014.v07.i01.p04)
The research aims is to collect a complete and accurate data and information concerning about the impact of marketing strategy. This study conducts an analysis to examine and analyze the execution of marketing strategy and sales and also to analyze how big the impact of marketing strategy determine the sales of coal in PT Cahaya Mantingan Nusantara Jakarta, in order to anticipate an intense competition. Correlation analysis concludes a strong and significant correlation between sales and marketing strategy. The determination coefficient shows that 52,25 percent of sales determined by marketing strategy.
Keywords: Marketing Strategy , Sales.